PENGGUNAAN MODEL PAIRING UNTUK MENINGKATKAN MOTIVASI, AKTIVITAS, DAN HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR PADA MATERI GEOMETRI - Herti Prastitasari; Jumadi; Erma Marhamah; Ratna Purwanti; Raihanah Sari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to determine the teachers' and students' learning activities, the students' motivation, and their learning outcomes through the PAIRING model in learning mathematics at elementary schools. The design of this study was classroom action researchcarried out at SDN Amparaya 2 for two cycles in four meetings. The results showed that the teachers' activities increased in cycles one and two with a score of 23 to 30 with very good criteria. Then, the students' activities in cycle one and cycle two classically increased from60% to 100%. The results of learning motivation in cycle one and cycle two increased from 77% to 93% with the criteria of high motivation. After that, the students' learning outcomes on the geometry material in cycle one and cycle two increased from 65% to 88% with the criteria for completion. The results of this study were expected to be used in learning to increase the learning activities, motivation, and learning outcomes in geometry material.